IDENTIFYING STUDENTS’ DIFFICULTIES IN READING COMPREHENSION AT SMA MUHAMMADIYAH 1 PALU THROUGH NARRATIVE TEXT - Rahmat Sudirman; Mawardin M. Said (Tadulako University, 2021)
To find out the students’ difficulties in comprehending Narrative text at the tenth grade of SMA Muhammadiyah 1 Palu.. This research applied a qualitative research design. The subject of this research were All the students of tenth grade at SMA Muhammadiyah 1 Palu and English teacher of tenth grade at SMA Muhammadiyah 1 Palu. The techniques used to get the data were questionnaire and an Interview Question. As the final result found from the students’ questionnaire of their reading problem, based on the result of the identification, it was found that students of SMA Muhammadiyah 1 Palu had difficulties in vocabulary and organization of narrative text, inappropriate reading strategies, lack of motivation, students’ insufficient background knowledge in reading narrative and bad reading process which the most common problem experienced by the students during the reading process was keeping their concentration. The data also supported by the interview with the teacher. Based on the results of the interview with the teacher, the students have problems in reading comprehension. The students’ problems in reading comprehension are: lack of vocabulary, slow reading speed, lack of motivation, and boredom. In case of reading narrative text, the students showed the following problems that they have less comprehension in grammar, lack of competence to find out the main information and specific information in the reading passage, lack of prediction ability or guessing meaning ability as well as lack of background knowledge about the reading passage, specifically on the background story or unfamiliar characters in the story.